Alokasi dan elastisitas belanja daerah tingkat II :: Studi komparatif di Propinsi Daerah Tingkat I Sumatera Barat - AMIR, Yohanes (Universitas Gadjah Mada, 1998)
Governmental unit on the system of goverment in the Republic of Indonesia recognize the existence of Kabupaten/Xotamadya Daerah Tingkat I1 as local autonomous, having responsibilities and right action to make public expenditure in term Grade I1 Local Cost. The Grade I1 Local cost must be allocated by routine and development cost by Grade I1 Local Goverment, in accordance with laws term. By the intensity and extensity of govermental affairs managed by Grade I1 Local Goverment, Grade I1 Local Cost have improvement in term growth. Balanced and dynamics budgetary principle applied focussed in the budgetary of local revenue and cost, deliver a number of fund allocated as growing local cost absolutely similar to the total of local revenue. The policy in allocation term of Grade I1 Local Cost of routine and development cost have specific relation, determination and elasticity for each Grade I1 Local. Relation, and development determination and elasticity of routine cost in Grade I1 Local are primary problems which will be analyzed at this research. Meanwhile, analysis unit of this research is 14 Kabupatenflotamadya Daerah Tingkat I1 in the Grade I Local Provinsi Sumatera Barat. Theoritical frame developt shows that Grade I1 Local Cost which consist of routine and development cost is dependent variabel having relations. I ' t s determinated by many spesific independent variabel. Routine cost is related and determined by (1) the total population (2) the total of the local original revenue, (3) the total of routine subsidy for the local autonomous, and ( 4) the evaluation output for the routine cost by Gubernur Kepala Daerah Tingkat I at the authoritative officials for this. Then, development cost as dependent vcariabel is related and determined by variabel ( 1) the total population ( 2) t he total of the local original revenue, and ( 3) t he total of development subsidy for the local autonomous. Researcher finds out that not all of relation and determination for the routine and the development cost at 14 Kabupaten/Kotamadya Daerah Tingkat I1 of Sumatera Barat have probability significant level convincingly. At the partially and simultaneously of dependent variabel of routine cost as the independent variabel, not all of Kabupatenflotamadya Daerah Tingkat I1 have convincingly probability significant grade. In many focus, not all of independent variabel partially and simultaneously have relation and determine development cost with convincingly probability grade at all of analysis unit.